2012
DOI: 10.1603/me12026
|View full text |Cite
|
Sign up to set email alerts
|

<I>Aedes aegypti</I> (Diptera: Culicidae) Biting Deterrence: Structure-Activity Relationship of Saturated and Unsaturated Fatty Acids

Abstract: In this study we evaluated the biting deterrent effects of a series of saturated and unsaturated fatty acids against Aedes aegypti (L), yellow fever mosquito (Diptera: Culicidae) using the K & Dbioassay module system. Saturated (C6:0 to C16:0 and C18:0) and unsaturated fatty acids (C11:1 to C14:1, C16:1, C18:1, and C18:2) showed biting deterrence index (BDI) values significantly greater than ethanol, the negative control. Among the saturated fatty acids, mid chain length acids (C10:0 to C13:0) showed higher bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 15 publications
5
69
0
Order By: Relevance
“…Studies have shown that vanillin reduces the evaporation rate of active ingredients and therefore extends the protection time (repellency) [15]. It is believed that vanillin changes the volatile composition of essential oils and also has an effect on the gustatory processes of mosquitoes [29,30]. In this study the effect of vanillin was often more evident at increased time after application.…”
Section: Discussionmentioning
confidence: 56%
“…Studies have shown that vanillin reduces the evaporation rate of active ingredients and therefore extends the protection time (repellency) [15]. It is believed that vanillin changes the volatile composition of essential oils and also has an effect on the gustatory processes of mosquitoes [29,30]. In this study the effect of vanillin was often more evident at increased time after application.…”
Section: Discussionmentioning
confidence: 56%
“…Brießy, the assay system consists of a six-well reservoir with each of the 3 by 4 cm wells containing 6 ml of blood. As described by Ali et al (2012), a feeding solution consisting of citrateÐphosphateÐ dextroseÐadenine (CPDA-1) and ATP was used instead of blood. Green ßuorescent tracer dye (www.blacklightworld.com) was used to determine the feeding by the females.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical Analyses. Proportion not biting was calculated as described by Ali et al (2012). As the K&D module bioassay system can handle only four treatments along with negative and positive controls, to make direct comparisons among more than four treatments and to compensate for variation in overall response among replicates, biting deterrent activity was quantiÞed as Biting Deterrence Index (BDI).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the assay system briefly consists of a six-well reservoir with each of the 3 9 4 cm wells containing 6 ml of blood. As described by Ali et al (2012), a feeding solution consisting of CPDA-1 and ATP was used instead of blood. Green fluorescent tracer dye (www.…”
Section: Mosquito Biting Bioassaymentioning
confidence: 99%
“…As the K&D module bioassay system can handle only four treatments along with negative and positive controls, in order to make direct comparisons among more than four test compounds and to compensate for variation in overall response among replicates, biting deterrent activity was quantified as Biting Deterrence Index (BDI) (Ali et al, 2012). The BDIs were calculated using the following formula:…”
Section: Statistical Analyses For Mosquito Biting and Larvicidal Bioamentioning
confidence: 99%